Imbestigador the best of Imbestigador, vol. 1 - Enriquez, Mike.; GMA News and Public Affairs ([Quezon City] GMA News and Public Affairs, 2006)
Compilation of the best episodes of the popular television documentary program "Imbestigador." Pobreng Pinoy, a shocking exposé on how Filipinos today cope with poverty -- PNP, isang pagsusuri, an insightful investigation of the country?s police force -- Juan tanga?, an unflinching look at the present state of (mis)education in the Philippines.
Pobreng Pinoy (34:32) -- PNP : isang pagsusuri (56:10) -- Juan Tanga (44:08) -- Special interview with Mike Enriquez.
Host, Mike Enriquez.
DVD.
In Tagalog.
Keywords: Poverty -- Philippines; Hunger -- Philippines; Squatters -- Philippines; Squatter settlements -- Philipppines; Health Services -- Philippines; Police corruption -- Philippines; Education -- Philippines; Philippines -- Social conditions